THE Hubungan Antara Deteksi Dini Pengenalan Gejala Awal Stroke Dengan Pengetahuan Tentang Cara Penanganan Stroke Pada Masyarakat Dalam Tindakan Pertolongan Pra Rumah Sakit di wilayah kerja Puskesmas Bakunase Kota Kupang - Istha Leanni Muskananfola; Sebastianus Kurniadi Tahu; Erna Ns. Febriyanti; Wiliam J. B. Lekitoo (Jurnal Keperawatan Malang, 2021)
ABSTRACT Background: Stroke is an emergency condition that can be life threatening and cause disability. Management of stroke patients is determined by treatment in the prehospital setting. Appropriate handling can be done by the community by recognizing the symptoms of changes in the face, extremities, and the ability to speak quickly. Purpose: Analyzing the relationship between early detection of early symptoms of stroke with knowledge of how to handle stroke in the community in pre-hospital aid action at Bakunase Community Health Center, Kupang City. Methods: This research is a quantitative study with a correlational analytic design and a cross sectional design. There were 121 respondents in RT 002, RW 001, Kelurahan Bakunase, Kupang City. Data collection using a questionnaire in November 2020. Result: The results of the analysis with the Spearman rho test obtained a p value of 0.011 with an R value of 0.231, which means that there is a significant relationship between early detection of early stroke symptom recognition and knowledge of how to handle stroke in the community in pre-hospital aid action in the working area of Bakunase Community Health Center, Kupang City. The R value of 0.231 indicates that the association between early detection of early stroke symptom recognition and knowledge of how to treat stroke is in the positive category with weak correlation strength. Conclusion: There is a relationship between early detection of early stroke symptom recognition and knowledge of how to treat stroke in the community. This study reveals that because knowledge for pre-hospital stroke management begins with the ability to recognize symptoms, the role of health agencies and educational institutions is needed to maximize health education for the public to be ready to deal with emergency conditions in the pre-hospital environment. Key words: Detectio;, Stroke; Pre-Hospital